2016
DOI: 10.3892/ol.2016.5239
|View full text |Cite
|
Sign up to set email alerts
|

Change in number and size of circulating tumor cells with high telomerase activity during treatment of patients with gastric cancer

Abstract: Abstract. Detection of circulating tumor cells (CTCs) in peripheral blood is useful for estimating the prognosis of patients with cancer. We previously reported the detection of CTCs by OBP-401, a telomerase-specific, replication-selective, oncolytic adenoviral agent carrying the green fluorescent protein (GFP) gene. We demonstrated that the number of large (L)-GFP+ cells (≥7.735 µm in diameter) in peripheral blood samples correlated significantly with the prognosis of treatment-naïve gastric cancer patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Moreover, pretreatment small cell CTCs (≥ 2/6 ml) were highly related to poor prognosis in advanced lung cancer patients. Though previous studies have documented the mesenchymal CTCs or CTCs in patients following therapeutic treatment were in small cell size (Hiroaki et al 2014; Ito et al 2016), few studies have been conducted to further investigate how diverse CTCs based on cell size correlate to clinical outcome due to the inherent drawbacks of the conventional CTCs technology. As far as we know, it is the first time in our study to report the dynamic change of small cell CTCs number correlated to treatment response and pretreatment small cell CTCs (≥ 2/6 ml) were significantly related to unfavorable clinical outcome in advanced lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pretreatment small cell CTCs (≥ 2/6 ml) were highly related to poor prognosis in advanced lung cancer patients. Though previous studies have documented the mesenchymal CTCs or CTCs in patients following therapeutic treatment were in small cell size (Hiroaki et al 2014; Ito et al 2016), few studies have been conducted to further investigate how diverse CTCs based on cell size correlate to clinical outcome due to the inherent drawbacks of the conventional CTCs technology. As far as we know, it is the first time in our study to report the dynamic change of small cell CTCs number correlated to treatment response and pretreatment small cell CTCs (≥ 2/6 ml) were significantly related to unfavorable clinical outcome in advanced lung cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…We also point out that the size distribution of the cultured cells might be different than actual tumor cells circulating in the blood, which can vary specially during treatment of patients. 28 We present our results in the following order: In Sec. IV, we discuss the breakdown of the separatrix.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Complementary techniques such as ISET (isolation by size of epithelial tumor cells), based on a direct size selection method for epithelial cell enrichment to further lter small CTCs may be applied to generate additional information. Research has shown the number of small CTCs is increased following chemotherapy and is accompanied by the increased ratio of drug-resistant to drug-sensitive CTCs [44]. CTMs, derived from oligoclonal groups of cells from the primary tumor, have a 23-to 50-fold increased metastatic potential compared to single CTCs [45].…”
Section: Discussionmentioning
confidence: 99%